Misconceptions About Negative Pressure Rooms and Their Impact Aboard USNS Comfort in New York City. (30th June 2020) - Hill, Christopher J.; Capra, Gregory G.; McDonald, Thomas P.; Santiago, Gabriel F.; Radabaugh, J. Paul
Abstract : The outbreak of novel coronavirus disease 2019 (COVID‐19) has had a momentous impact on the field of otolaryngology due to the high number of aerosol‐generating procedures involving the upper aerodigestive tract. These procedures bear significant risk to the provider and clinical environment due to the possibility of viral aerosolization. While significant attention has been appropriately paid to personal protective equipment during this pandemic, an understanding of industrial hygiene is also necessary for the safe delivery of health care to mitigate the risk of exposure to other patients and health care workers. We provide a review of air ventilation practices and their role in reducing pathogen spread. In addition, we share our experiences with effectively treating COVID‐19–positive patients aboard the USNS Comfort through proper environment control measures.